User guide to seed tracing. RTB User Guide - Kilwinger, Fleur B.M.; Buddenhagen, C.E. (International Potato Center, 2021)
Seed tracing can be used to map seed flows in a seed system, and to gain insights about how actors diffuse seeds and named varieties. Actors might include growers, seed multipliers and variety developers. Seed tracing can also examine the flow of information, money, ideas, or pests and diseases that might hitchhike on the exchanged seed. The data set can also form the basis of an Impact Network Analysis (INA): it forms the minimum data set, which involves modelling about the flow of seed, diseases, or information through the system. See RTB user guide to Impact Network Analysis (INA) for further details. Network data usually consist of nodes and edges. In a seed network analysis, the nodes represent actors who exchange seed or knowledge about it. The transactions between them form the edges. Depending on the research question, a range of information on the nodes and edges can be collected. Node information can be the types of actors, their location, demographic information, etc. Edge information can be the varieties and quantities of seed shared, data of the transaction, etc. Before collecting data, it is important to have a clear research design describing what to trace, who to sample and within what timeframe. The collected data can be analyzed using various software packages such as R and Excel.